Expression of Immunity- and Stress-Related Genes during an Intermolt Period in the Colorado Potato Beetle - Vadim Yu. Kryukov; Ulyana N. Rotskaya; Olga N. Yaroslavtseva; Yury A. Noskov; Viktor V. Glupov (Insects, 2022)
Different developmental stages of insects may be dissimilar in immunity functioning. Additionally, the stages often inhabit diverse environments with specific microbial communities. In the Colorado potato beetle, a strong increase in resistance to entomopathogenic fungi is observed during the intermolt period of last-instar larvae, but mechanisms of this change are insufficiently understood. We studied changes in the expression of immunity- and stress-related genes in the fat body and integument during this intermolt period by quantitative PCR. By the end of the instar, there was upregulation of transcription factors of Toll, IMD, and Jak–Stat pathways as well as genes encoding metalloprotease inhibitors, odorant-binding proteins, and heat shock proteins. Nonetheless, the expression of gene LdRBLk encoding β-lectin did not change during this period. Most of the aforementioned genes were upregulated in response to Metarhizium robertsii topical infection. The expression alterations were more pronounced in recently molted larvae than in finishing feeding larvae and in the integument compared to the fat body. We believe that upregulation of immune-system- and stress-related genes at the end of the intermolt period is an adaptation caused by migration of larvae into soil, where the probability of encountering entomopathogenic fungi is high.